Avaliação de postes de Eucalyptus retirados da rede elétrica por microscopia eletrônica de varredura e ensaios de flexão - Abruzzi, Rafael Colombo (2012)
This paper presents results of tests on poles of wood of different species of Eucalyptus, new and removed from the network of distribution of electric energy in southern Brazil. Are presented correlations between mechanical properties, density, state of deterioration and lumen diameter of Eucalyptus poles. The state of deterioration was determined by field inspections. Poles in various states of deterioration were removed from the network for static bending tests and density measurements. Analysis of the lumen diameter were performed by scanning electron microscopy to correlate the density with the wood anatomy and identification of the treatment used as a preservative. The mechanical tests indicated that the average values of bending strength and stiffness decline with the deteriorating state of Eucalyptus. But, there was a large variation in these measures influenced by the density of the wood. Less dense woods presented low residual mechanical strength even though not presenting signs of deterioration. This study indicated that the state of deterioration measured by field inspection alone is not a good indicator for predicting the durability of eucalyptus structures, making necessary a preliminary analysis of the density. The data obtained from SEM/EDX about chemical treatment and morphological characterization of wood structures come to complement the data obtained through inspection that allowed a real evaluation of the deterioration of these poles on the network.